2022
DOI: 10.1007/s00266-022-02944-1
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Surgeons and their Financial Relationships with the Industry in the era of COVID: Insights from the Physician Payments Sunshine Act

Abstract: Background The impact of the COVID-19 pandemic on physician relationships with industry and subsequent financial implications has not been previously assessed. The aim of this study is to compare pre-and post-COVID-19 payments between industry and medical providers for all plastic surgeons. Methods Payment information was collected for the 2019 and 2020 reporting periods from the Open Payments Program (OPP) database for plastic surgeons and plastic surgeon subspecialists. An analysis was performed of trends an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Concordant with our ndings, a study from Murayama et al evaluating changes in general payments to rheumatologists pre-and postpandemic found that the total value of general payments and the number of rheumatologists receiving general payments both decreased signi cantly after the onset of the pandemic [19]. Other publications reporting industry payments to plastic surgeons or infectious disease physicians before and after the onset of the pandemic show similar trends [20,21]. Within the general category, the mean payment to ophthalmologists for consulting fees, education, faculty or speakers, food and beverage, gifts, honoraria, royalty or license, and travel and lodging all decreased signi cantly (p < 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Concordant with our ndings, a study from Murayama et al evaluating changes in general payments to rheumatologists pre-and postpandemic found that the total value of general payments and the number of rheumatologists receiving general payments both decreased signi cantly after the onset of the pandemic [19]. Other publications reporting industry payments to plastic surgeons or infectious disease physicians before and after the onset of the pandemic show similar trends [20,21]. Within the general category, the mean payment to ophthalmologists for consulting fees, education, faculty or speakers, food and beverage, gifts, honoraria, royalty or license, and travel and lodging all decreased signi cantly (p < 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…This was followed by declines in dollars, payments, and specialists paid in 2020 and 2021, which could be explained by the onset of the COVID‐19 pandemic. Other analyses of the Open Payments Database have also reported sudden decreases in payments during this time frame for a number of specialties 15–17 . As more data becomes available in the coming years and we move past pandemic restrictions, future research should assess whether industry payments have recovered.…”
Section: Discussionmentioning
confidence: 88%
“…Other analyses of the Open Payments Database have also reported sudden decreases in payments during this time frame for a number of specialties. 15 , 16 , 17 As more data becomes available in the coming years and we move past pandemic restrictions, future research should assess whether industry payments have recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, significant practice changes occurred, including a 60% decline in office-based interactions within the first month of the pandemic, and overall hospital losses estimated at $323.1 billion dollars for the 2020 year. 3 With precipitous declines in provider services across all medical and surgical specialties, 4 we hypothesized that industry-provider payments would decrease as well. In fact, our analysis showed just that.…”
Section: Discussionmentioning
confidence: 99%